NEUROD1: transcriptional and epigenetic regulator of human and mouse neuronal and endocrine cell lineage programs - Pavlinkova, Gabriela; Smolik, Ondrej (Frontiers in Cell and Developmental Biology, 2024)
Transcription factors belonging to the basic helix-loop-helix (bHLH) family are key regulators of cell fate specification and differentiation during development. Their dysregulation is implicated not only in developmental abnormalities but also in various adult diseases and cancers. Recently, the abilities of bHLH factors have been exploited in reprogramming strategies for cell replacement therapy. One such factor is NEUROD1, which has been associated with the reprogramming of the epigenetic landscape and potentially possessing pioneer factor abilities, initiating neuronal developmental programs, and enforcing pancreatic endocrine differentiation. The review aims to consolidate current knowledge on NEUROD1’s multifaceted roles and mechanistic pathways in human and mouse cell differentiation and reprogramming, exploring NEUROD1 roles in guiding the development and reprogramming of neuroendocrine cell lineages. The review focuses on NEUROD1’s molecular mechanisms, its interactions with other transcription factors, its role as a pioneer factor in chromatin remodeling, and its potential in cell reprogramming. We also show a differential potential of NEUROD1 in differentiation of neurons and pancreatic endocrine cells, highlighting its therapeutic potential and the necessity for further research to fully understand and utilize its capabilities.